Barriers to Medical Record Information Disclosure for Private Health Insurance Claims: A 5M Factor Analysis at Mitra Sejati General Hospital, Medan - Puput Melati Hutauruk; Valentina Valentina; Lisa Anggriani Tanjung; Atikah Nadiah Syafei; Havija Sihotang (Cattleya Darmaya Fortuna, 2026)
The release of medical record information is a critical component of the private health insurance claim process, as it is closely related to document completeness, patient data confidentiality, and the timely reimbursement of healthcare services. Incomplete medical record documentation may result in claim rejection or resubmission, leading to delays in reimbursement and reduced administrative efficiency within hospitals. This study aimed to analyze the barriers to the release of medical record information for private health insurance claims based on the 5M framework (Man, Material, Method, Machine, and Money) at Mitra Sejati General Hospital, Medan. A qualitative study with a case study approach was employed. Three informants were purposively selected, consisting of one Head of the Insurance Unit and two medical record information release officers directly involved in the insurance claim process. Data were collected through in-depth interviews, direct observation, and document review, and were analyzed using the interactive model of Miles and Huberman. The findings revealed that, of the 490 private insurance claim files submitted, 384 (78%) were complete, while 106 (22%) were incomplete. The primary cause of incomplete claims was incomplete medical discharge summaries (44%). The main barriers were associated with the Man factor, including an insufficient number of personnel, inadequate verification of document completeness, and delays in completing discharge summaries by the attending physicians. The Material and Method factors also contributed to claim delays due to incomplete supporting documents and the absence of detailed standard operating procedures specifically governing the release of medical record information for private insurance claims. In contrast, the Machine and Money factors were not identified as significant barriers because adequate facilities and financial support were available. The study concludes that improving the quality of medical record documentation, optimizing human resources, and developing more comprehensive standard operating procedures are essential strategies for enhancing the effectiveness of medical record information release in the private health insurance claim process.